Tell me something I don't already know: Learning in low- and high-inflation settings - Michael Weber; Bernardo Candia; Tiziano Ropele; Rodrigo Lluberas; Serafin Frache; Brent Meyer; Saten Kumar; Yuriy Gorodnichenko; Dimitris Georgarakos; Olivier Coibion; Geoff Kenny (Federal Reserve Bank of Atlanta, 2023)
Using randomized control trials (RCT) applied over time in different countries, we study how the economic environment affects how agents learn from new information. We show that as inflation has risen in developed economies, both households and firms have become more attentive and informed about inflation, leading them to respond less to exogenously provided information about inflation and monetary policy. This observation holds for both firms and households. We also study the effects of RCTs in countries where inflation has been consistently high (Uruguay) and low (New Zealand) as well as what happens when the same agents are repeatedly provided information in both low- and high-inflation environments (Italy). Our results broadly support models in which inattention is an endogenous outcome that depends on the economic environment.
Keywords: E3; E4; E5; 330; inattention; RCTs; inflation expectation; Inflationserwartung; Wirtschaftsinformation; Geldpolitik; Rationale Erwartung; Randomisierte kontrollierte Studie